Communicative Question Evasion Tactics in Scientific Discourse - Zadvornaya, Jelena G. (Respectus Philologicus, 2006)
The article is centred on the forms of realisation of communicative question evasion tactics in scientific discourse. In total., 12 tactics are singled out and analysed (ignoring the question, explicit refusal to answer, criticism of the question, rephrasing the question, topic switching, etc.). The analysis of the tactics results in defining the communicative pragmatic factors that account for the specificity of their realization in scientific communication: the responder’s epistemic state, his/her situational communicative intentions, etc. The author shows that the participants’ communicative behaviour in the situation of question. Evasion, on the whole, complies with common communicative conventions governing scientific discourse (the demands for cooperation, politeness, tolerance) and conforms to its fundamental communicative intentions. Including the joint search for verity and the elaboration of knowledge.